A Prospective Study On the Surgical Treatment of Large Hypertensive Basal Ganglia Bleed: Surgical Treatment of Large Hypertensive Basal Ganglia Bleed - Munwar Ali, Muhammad; Muzaffer uddin , Muhammad; Shibli, Zaheen; Kumar, Ramesh; Muhammad Zeeshan, Qazi; Zulfiqar, Farrukh (Pakistan Journal of Health Sciences, 2022)
Spontaneous intracerebral bleed is a communal subtype of stroke and is usually the deadliest. Objective: To determine the efficacy of surgical management of spontaneous hypertensive basal ganglia bleed and the factors contributing its outcome. Methods: A prospective study was carried out in the department of Neurosurgery for two-year duration from January 2020 to December 2021. 80 patients aged 18-65 years were included after matching criteria of inclusion of this study. The open craniotomy and evacuation was the surgical technique in all patients. After treatment, all cases were followed up for minimum six months. Patients were categorized as having good or bad scores on GOS. The data analysis was done using SPSS by assessing the effect of the observed variables including age, GCS, volume of blood, midline shift, ventricular extension and hydrocephalus. Results: 80 patients, 55 (68.8%) males and 25 (31.2%) females were done with surgical intervention. Their ages ranged from 18-65 years. Conferring to the patients GCS, they were divided into 3 groups: 26 (32.5%) patients with 5-8GCS; 38 (47.5%) patients with 9-12 GCS; and 16 (20%) patients with 13-15GCS. The volume of blood ranged from 30-90 cm3. 13 patients (16.3%) had ventricular extension, and 9 patients had hydrocephalus. In 34 patients (42.5%) had midline shift was <5 mm and 46 patients (57.5%) had > 5 mm. 49 patients (61.3%) had favorable results conferring to GOS scoring (4, 5), poor results in 31 (38.7%) cases, and 21 among those died (26.3%). Conclusions: Early evacuation with surgery results in a radical decrease in intracranial pressure and better prognosis. Patients with midline deviation >5mm, ventricular extension, hydrocephalus and reduced level of consciousness have worst prognosis.